Hyperspectral image processing system - Mahmouei, Sahar Sabbaghi (2012)
Hyperspectral imaging system is a new technique, which provides an alternative way to increasing the accuracy by adding another dimension: the wavelength. Recently, hyperspectral imaging is also finding its way into many more applications, ranging from medical imaging in endoscopy for cancer detection to quality control in the sorting of fruit and vegetables. But effective use of hyperspectral imaging requires an understanding of the nature and limitations of the data and of various strategies for processing and interpreting it. Also, the breakthrough of this technology is limited by its cost, speed and complicated image interpretation. We have therefore initiated work on designing real-time hyperspectral image processing to tackle these problems by using a combination of smart system design, and pseudo-real time image processing software. Traditional hyperspectral imaging systems acquire one-dimensional spectral images and require relative motion of sensor and scene in addition to data processing to form a two-dimensional image cube. There is much interest in developing hyperspectral imagers based on unique prism-grating-prism (PGP) optical design that acquire a 2D dimensional spectral image can be formed and build up an image cube as a function of time. The main focus of this saraeser is the development of hyperspectral imaging system for laboratory or stationary remote sensing applications. The system consists of a high performance digital CCD camera, an intelligent processing unit, an imaging spectrograph, an optional focal plane scanner and a laptop computer equipped with a frame-grabbing card. In addition, special software has been developed to synchronize between the frame grabber (video capture card), and the digital camera with different image processing techniques for both digital and hyperspectral data. The CCD camera provides 1280(h) x 1024(v) pixel resolution and true 12-bit dynamic range. The imaging spectrograph is attached to the camera via an adapter to disperse radiation into a range of spectral bands. The effective spectral range resulting from this integration is from 400 nm to 1000 nm. The optional focal plane array can be attached to the back of the spectrograph via C-mount for stationary image acquisition. The camera and the frame grabbing board are connected via a PCI interface board, and the utility software allows for complete camera control and image acquisition. The imaging system captures one line image for all the bands at a time and a focal plane array serves as a mobile platform to carry out pushbroom scanning in the along-track direction. Preliminary image acquisition testing indicates that this CCD camera-based hyperspectral imaging system has potential for agricultural and food industry applications.